Floppy but not sloppy: interaction mechanism of FG-nucleoporins and nuclear transport receptors - Aramburu, Iker Valle; Lemke, Edward A. (Seminars in cell & developmental biology, 2017)
The nuclear pore complex (NPC) forms a permeability barrier between the nucleus and the cytoplasm. Molecules that are able to cross this permeability barrier encounter different disordered phenylalanine glycine rich nucleoporins (FG-Nups) that act as a molecular filter and regulate the selective NPC crossing of biomolecules. In this review, we provide a current overview regarding the interaction mechanism between FG-Nups and the carrier molecules that recognize and enable the transport of cargoes through the NPC aiming to understand the general molecular mechanisms that facilitate the nucleocytoplasmic transport.
Gesehen am 24.09.2018